Imaginary plots and political realities in the plays of William Congreve - Novak, Maximillian E. 1930- (Anthem Press, 2020)
William Congreve was deeply involved in the events of his turbulent times. That involvement reveals itself in works which have sometimes been regarded as entirely unengaged with the realities of his society. This book attempts to read Congreve's plays and his novella, Incognita, against the political and social upheaval of the period initiated by the rebellion of 1688. A strong supporter of the new world ushered in by William III and Mary, Congreve fought against the reactionary politics of the Jacobite opposition
Title from publisher's bibliographic system (viewed on 17 Jul 2020)
Keywords: Congreve, William / 1670-1729 / Criticism and interpretation